The Illustrations of Indigenization of Islam in Indonesian Cultural Landscape - Dody S. Truna (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This study discusses how religious development in Indonesia has resulted in switching the function of purity to non-purity in religious practices. Using a phenomenological approach, this review finds that some Muslims maintain their purity for various reasons, but some mix their beliefs with the local culture. This situation leads to the following study on a macro scale about Islam's indigenization in Indonesia's cultural landscape. This study found a relatively high cultural acculturation between Islam as a global religion and local Indonesian culture. The community reinforces this acculturation by promoting traditional leaders and the need for a sense of security that has been embedded in local communities.